Banish fat boost metabolism [videorecording (DVD)] - Ambandos, Andrea; Michaels, Jillian (Lions Gate Films, 2009)
This 40-minute circuit workout blasts your heart rate with challenging intervals to turn up the burn and peel off the pounds. Whether you're just getting started, or ready for a hardcore workout, this program will ignite your metabolism and more.